2008
DOI: 10.1099/jmm.0.47705-0
|View full text |Cite
|
Sign up to set email alerts
|

Signal-mediated interactions between Pseudomonas aeruginosa and Candida albicans

Abstract: Pseudomonas aeruginosa causes infections in a wide variety of hosts and is the leading cause of mortality in cystic fibrosis (CF) patients. Although most clinical isolates of P. aeruginosa share common virulence determinants, it is known that strains evolve and change phenotypically during CF lung infections. These changes can include alterations in the levels of N-acyl homoserine lactones (HSLs), which are secreted signal molecules. In the CF lung, fungi, especially Candida albicans and Aspergillus fumigatus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 63 publications
5
123
0
1
Order By: Relevance
“…These two organisms share ecological niches, and both produce signals capable of interfering with the production of virulence factors by the other. Production of 3-oxo-C 12 -HSL by P. aeruginosa inhibits C. albicans filamentation, a crucial virulence adaptation for the development of opportunistic infections (90), while production of the fungal metabolite farnesol reduces PQS and pyocyanin levels and swarming motility in P. aeruginosa (39,132). The slight structural resemblance (C 12 FIG 6 PVD signaling pathway in P. aeruginosa.…”
Section: Cross-kingdom Signalingmentioning
confidence: 99%
“…These two organisms share ecological niches, and both produce signals capable of interfering with the production of virulence factors by the other. Production of 3-oxo-C 12 -HSL by P. aeruginosa inhibits C. albicans filamentation, a crucial virulence adaptation for the development of opportunistic infections (90), while production of the fungal metabolite farnesol reduces PQS and pyocyanin levels and swarming motility in P. aeruginosa (39,132). The slight structural resemblance (C 12 FIG 6 PVD signaling pathway in P. aeruginosa.…”
Section: Cross-kingdom Signalingmentioning
confidence: 99%
“…Accordingly, and as previously underlined, infections of the CF airways is highly polymicrobic and there is growing evidence that many of these microorganisms interact (Sibley & Surette, 2011) as observed between P. aeruginosa and S. aureus (Biswas et al, 2009;Hoffman et al, 2006;Mitchell et al, 2010b;Qazi et al, 2006;Yang et al, 2011), P. aeruginosa and Burkholderia spp. (Bakkal et al, 2010;Chattoraj et al, 2010;Riedel et al, 2001;Weaver & Kolter, 2004), P. aeruginosa and S. maltophilia , P. aeruginosa and C. albicans (McAlester et al, 2008), and more generally with a large proportion of the organisms found in the CF airways (Duan et al, 2003;Sibley et al, 2008).…”
Section: Interspecies Interactions Between Cf Pathogensmentioning
confidence: 99%
“…Hyphae development in C. albicans can be inhibited by 3-oxo-C12-homoserine lactone from Pseudomonas aeruginosa (Hogan et al, 2004), the S. mutans pheromone CSP (competence-stimulating peptide) (Jarosz et al, 2009) or by the diffusible signal factor trans-2-decenoic acid (Vilchez et al, 2010). Conversely, the signalling molecule farnesol from C. albicans inhibits the swarming motility of P. aeruginosa (McAlester et al, 2008) and induces the Pseudomonas quinolone signal synthesis (Cugini et al, 2010). No report exists of the induction of the quorum sensing signalling circuit of an oral pathogen by a eukaryotic fungus.…”
Section: Introductionmentioning
confidence: 99%